2016
DOI: 10.5539/hes.v6n2p19
|View full text |Cite
|
Sign up to set email alerts
|

Developing Research Paper Writing Programs for EFL/ESL Undergraduate Students Using Process Genre Approach

Abstract: Research Paper Writing (RPW) plays a key role in completingall research work. Poor writing could lead to the postponement of publications. Therefore, it is necessary todevelop a program of (RPW) to improve RPW ability for EFL/ESL writers, especially for undergraduate students in Higher Education (HE) institutions, which has caught less attention of curriculum developers so far. Therefore, this studyaims to determine the core components of (RPW) program perceived as essential for EFL/ESL undergraduate studentsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In summary, the findings of this study were somewhat contradictory to the previous findings of related studies that supported the effectiveness of the process genre approach (e.g., Badger & White, 2000;Garnica & Torres, 2015;Handayani & Siregar, 2013;Tuyen, Osman, Dan, & Ahmad, 2016). This study provided conclusive evidence for the approach not being fully efficient in developing EFL learners' CAF.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In summary, the findings of this study were somewhat contradictory to the previous findings of related studies that supported the effectiveness of the process genre approach (e.g., Badger & White, 2000;Garnica & Torres, 2015;Handayani & Siregar, 2013;Tuyen, Osman, Dan, & Ahmad, 2016). This study provided conclusive evidence for the approach not being fully efficient in developing EFL learners' CAF.…”
Section: Resultscontrasting
confidence: 99%
“…The present study has shown only a partial impact of the process genre approach on Saudi advanced EFL undergraduates' reactions, production accuracy, and lexical variation. Most of the previously mentioned findings showed that the process genre approach was meaningfully effective in developing the writing skills of EFL learners (e.g., Arteaga-Lara, 2017;Handayani & Siregar, 2013;Tuyen, Osman, Dan, & Ahmad, 2016;Voon, 2007;Zhang, 2018). Such partial evidence can be supported by the recent research findings that advocate activating the use of the process genre approach to improve learners' CAF constructs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Even though this approach has been studied in many EFL contexts (e.g., Babalola, 2012;Gupitasari, 2013;Pujianto, Emilia, & Ihrom, 2014;Tuyen, 2016;Ghufron, 2016;Saputra & Marzulina, 2016), to the best of the researcher's knowledge no records have been found for studies in the Yemeni or any other Arab EFL context. This research paper, therefore, attempts to study the use of the PGA in teaching report writing for Yemeni EFL students in a computer science department.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed improvements in the quality of student writing using PGA. Tuyen, Osman, Dan, & Ahmad (2016) aimed at determining the core components of Research Paper Writing (RPW) program for EFL/ ESL students using Process Genre Approach. Employing Delphi Technique, data from interviews with experts from a university in Vietnam and another one from Malaysia were analyzed.…”
Section: Previous Studiesmentioning
confidence: 99%